The Effectiveness of Graphic Organizers and Gist Strategies on Students with Different Reading Habits in Reading Comprehension - Ayiz, Abdul; Warsono, Warsono (Universitas Negeri Semarang, 2018)
This study is an experimental research with a factorial design addressed to investigate the effectiveness of graphic organizers and GIST strategy to enhance reading comprehension of students with good and poor reading habits. The samples of this study were the twelfth graders of MA Sholahuddin Demak in the academic year of 2016/2017. There were two classes that became the samples of the study. Graphic organizers strategy was used in the first experimental group, and GIST strategy was used in the second experimental group. To answer research questions number one up to four, T-test was used; meanwhile, two-ways ANOVA with F-test at the 5% (0.05) level of significance was used to answer the fifth up to seventh question. The result of this study showed that graphic organizers and GIST strategy were effective to enhance reading comprehension of students with good and poor reading habits. In addition, there is no significant difference of the use of graphic organizers and GIST strategies to enhance reading comprehension for students with good and poor reading habits. In addition, there is no significant difference of reading habits in using graphic organizers and GIST strategies to enhance reading comprehension. At last, there is no interaction among graphic organizers, and GIST strategies, reading comprehension, and reading habits.